Police powers and accountability in China and Hong Kong: a comparative perspective. Issue 3 (30th September 2014) - Chan, Ray
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to study police powers and accountability from a comparative perspective in both China and Hong Kong. Design/methodology/approach – This paper compares and contrasts police powers and accountability. Findings – The implications are many, including different political systems in which China is more authoritarian or paternalistic whereas Hong Kong is more pluralistic; checks and balances mechanisms in Hong Kong are far greater than in China; and the concept of accountability to the public is different in that Hong Kong police are accountable to members of the public but the mainland Chinese police force has a limited and top-down concept of accountability. Originality/value – An original comparative approach to policing in Hong Kong and China.